Activation of Nav1.1 ameliorates tau pathology and brain atrophy in a mouse model of tauopathy: Nonhuman/Target identification and validation studies: Tau. (7th December 2020) - Sampei, Kazuaki; Seki, Chie; Takuwa, Hiroyuki; Maeda, Jun; Ono, Maiko; Tokunaga, Masaki; Shimojo, Masafumi; Honda, Shigeyuki; Kimura, Taeko; Ishikawa, Taizo; Kudo, Takehiro; Takado, Yuhei; et al.
Abstract: Background: Several clinical studies indicate that subclinical epileptiform discharge is observed in patients with Alzheimer's disease (AD), and neuronal hyperexcitability accelerates their cognitive decline. Previous studies indicated that the expression level of Nav1.1, which is coded by the Scn1a gene and a voltage‐gated sodium channel abundantly expressed in parvalbumin‐positive inhibitory neurons, decreased in AD patients. Because it is reported that excitatory neural activity stimulates tau release from neurons, we hypothesized that suppressing neuronal hyperexcitability by enhancing inhibitory neural activities could ameliorate disease progression in a mouse model of tauopathy. In this study, we investigated if our in‐house Nav1.1 potentiator, compound‐X, prevents the progression of tau accumulation and neurodegeneration in a mouse model of tauopathy, rTg4510. Method: We performed electrophysiological recording to determine the specificity and potency of compound‐X in cells stably expressing various Nav subtypes, and cortical slices of Scn1a<+/‐> and rTg4510 mice. We subsequently tested the in‐vivo effects of compound‐X on Nav1.1 by examining if compound‐X can prevent hyperthermia‐induced seizure in Scn1a<+/‐> mice. To assess the effect of compound‐X on tau‐induced neuropathologies in rTg4510 mice, we orally treated rTg4510 mice with this compound from 4 months of age, and evaluated tau accumulation and brain atrophy of these animals by longitudinal tau PET with [ 18 F]PM‐PBB3 and MRI, respectively, at 6 and 8 months of age. Result: The auto‐patch‐clamp system using Nav stably expressing cells and current‐clamp recoding using cortical slices demonstrated that compound‐X could potentiate Nav1.1 current in a concentration‐dependent manner, leading to activation of inhibitory neurons. Scn1a<+/‐> mice administered with compound‐X showed an increased threshold of the rectal temperature of hyperthermia‐induced seizure, and prolonged latency to seizure, indicating that compound‐X can potentiate Nav1.1 in vivo. Significantly, tau accumulation and neuronal loss assessed by cerebral atrophy and lateral ventricular enlargement were profoundly suppressed in the brains of rTg4510 mice relative to vehicle‐treated controls. Conclusion: Pharmacological enhancement of inhibitory neuronal function can be a beneficial approach to the prevention of hyperexcitability‐mediated tau pathologies and neuronal death in a mouse model of tauopathy.